ナンキョク ショウワ キチ ニ オケル チョウ コウセイノウ ジシンケイ ニ ヨル コウタイイキ コウカンド ジシン カンソク -ダイ 33 ジ カンソクタイ ホウコク 1992- - 金尾, 政紀; カナオ, マサキ; 神沼, 克伊; カミヌマ, カツタダ; Kanao, Masaki; Kaminuma, Katsutada (1993)
P(論文) 南極・昭和基地においては, 第30次日本南極地域観測隊(JARE-30)により1989年にSTS (Streckeisen Seismometer)による地震観測システムが設置され, 広帯域高感度広ダイナミックレンジ地震観測が開始された。JARE-31,32には観測上の問題点をふまえてシステムに改良が加えられた。JARE-33では, 前年度までの観測方式を継続すると共にSTSを定常観測へ移行するための準備として以下の項目を実施した。1) BRB (Broad-Band)のアナログ, 及びデジタル収録を継続した。2) LP (Long-Period)のデジタル収録を開始した。3) NNSS (Navy Navigation Satellite System)に代わる, GPS (Global Positioning System)受信機による刻時信号の取り込みを新たに試みた。4) 温度変化に対するPOS (Position)のドリフトを, アナログモニターにより考察した。5) 設置状況を工夫し上下動2台の平行観測によりノイズ発生の原因を追求した。本稿ではJARE-33でのSTS観測システムによる観測報告として, 得られた波形を簡単に紹介すると共に観測上の種々の問題点についても言及する。 A three component Streckeisen Seismometer (STS) was tested during wintering of the 30th Japanese Antarctic Research Expedition (JARE-30,from April 1989) at Syowa Station (69°S, 39°E), East Antarctica. The broadband and wide dynamic-range digital seismic recording was started from May 1990 by JARE-31. During the wintering season of JARE-33 (from February 1992 to January 1993), both installation conditions and data-acquisition system were improved as follows : 1) BRB (Broad-Band) velocity output was monitored by thermal pen-recorders and the digital recording system. 2) Digital recording system of LP (Long-Period) acceleration output was started. 3) UT (Universal Time) system was replaced by GPS (Global Positioning System) satellites instead of NNSS (Navy Navigation Satellite System). 4) Relation between the drift of the pendulum and temperature change was investigated by monitoring POS (Position) output. 5) Comparison of two vertical sensors under different installation conditions revealed the nature of characteristic noises. In this paper, the results of JARE-33 observations are presented. Some problems concerning maintenance of the observation system remain unsolved. departmental bulletin paper